Rational Drug Design of Axl Tyrosine Kinase Type I Inhibitors as Promising Candidates Against Cancer - Sarukhanyan, Edita; Shityakov, Sergey; Dandekar, Thomas (Frontiers in Chemistry, 2020)
The high level of Axl tyrosine kinase expression in various cancer cell-lines makes it an attractive target for the development of anti-cancer drugs. In this study, we carried out several sets of in silico screening for the ATP-competitive Axl kinase inhibitors based on different molecular docking protocols. The best drug-like candidates were identified by their highest affinity to the target protein, after parental structure modifications. We found that our newly designed compound R5, a derivative of the R428 patented analog, is the most promising inhibitor of the Axl kinase according to three molecular docking algorithms applied in the study. The molecular docking results are in agreement with molecular dynamics simulations using the MM-PBSA/GBSA implicit solvation models, which confirms high affinity of R5 towards the protein receptor. Additionally, the selectivity test against other kinases reveals high affinity of R5 also towards ABL1 and Tyro3 kinases, emphasizing its promising potential for the treatment of malignant tumors.